Differentiated Leadership Styles in Vocational Education to Improve Learning Quality at SMK YPT 1 Purbalingga - Bambang Sudarsono; Sarwan Sarwan; Achadi Budi Santoso (Bulletin of Pedagogical Research, 2025)
Principal leadership has huge implications for school quality. The success of leadership is highly dependent on the variety of styles displayed by the principal. The purpose of this study is to uncover the pattern of development of various leadership styles that have been carried out by the principal in the context of independent learning. This article analyzes the quality of education with its influence on various leadership styles in an educational institution. With a focus on leadership style in improving the quality of education. The researcher aims to investigate the extent to which leadership style can influence the quality of education. The research method used includes literature analysis. The results of the study show that a good and firm leadership style can create a harmonious educational environment. Several leadership styles that are applied tend to have an influence on improving the quality of education. For example, a leadership style that is inspirational, inclusive, visionary, humanistic, and supports the participation of school residents can create a conducive environment for developing potential and improving the quality of education.